Pengajaran Membaca Al-Quran pada Etnik Melayu di desa Teluk Batang Kabupaten Kayong Utara - Nazril Hijar; Sukino; Abdul Mukti (At Turots: Jurnal Pendidikan Islam, 2023)
In the Malay community of Teluk Batang Village, North Kayong Regency (KKU), only a few parents enroll their children in Quranic schools (TPA) or hire Quranic tutors to teach at home. The majority, however, opt to send their children to a local "guru ngaji" or Quranic tutor in the village. It is commonly assumed by most parents that the Quran is sacred, and therefore, only individuals with religious knowledge authority ("holy people") are deemed appropriate to teach the sacred text. This study employs a qualitative approach, collecting data through interviews and non-participant observations. The primary sources of data are parents and local Quranic tutors serving as key informants. The research concludes that the primary goal of parents in educating their children in Quranic studies is to attain the "blessings" of the Quran and knowledge, which they believe is not acquired spontaneously but rather through intermediaries, one of which is the Quranic tutor. The village Quranic tutors employ the "sorogan" method in Quranic reading lessons, complemented by other activities such as the "becerak" ceremony, the administration of "healing water," and other elements that collectively form an integrated learning process.